The Effect of the Teams Games Tournament (TGT) Cooperative Learning Model on the Learning Motivation of Grade IX Students in the Akidah Akhlak Subject at MTsN 5 Karawang - Milla Aulya Milla; Akil; Ajat Rukajat (al-Afkar, Journal For Islamic Studies, 2026)
The learning process that is just listening, doing assignments and only focusing on books causes the classroom atmosphere to become monotonous and less actively involved in students. As a result, students become more passive, less enthusiastic, and face difficulties in understanding and internalizing the material being taught. This affects the low motivation of students to learn. This study aims to assess whether there is an impact of the Teams Games Tournament (TGT) type cooperative learning model on the learning motivation of students in grade IX in the Akidah Akhlak lesson. The method used in this study is quantitative experiment, included in the category of pseudo-experiment with a nonequivalent group design that contains pretest, posttest, and two treatments. The test results carried out in this study included descriptive analysis, normality test, homogeneity, and hypothesis testing using independent sample t-test. From the results of the study, it can be seen that in the descriptive analysis between the experimental classes there was an increase of 29,96 while the control class was worth 18,23. In the normality test, both the experimental and control classes showed a normal distribution because the data produced > 0,05, in the homogeneity test the pretest based on mean value 0,197 and the posttest value 0,234 can be concluded to be homogeneous, in the hypothesis test the sig value. 0,000 < 0,05 showed the influence of the Teams Games Tournament (TGT) type cooperative learning model on students' learning motivation in the Moral Faith lesson.